Ptosis and Mass Like Lesions in Behçet’s Disease: A Rare Presentation - Seher KIR; Lütfi AKYOL; Metin ÖZGEN; Hediye PINAR GÜNBEY; Mehmet SAYARLIOĞLU (Archives of Rheumatology, 2018)
In this article, we describe a case of neuro-Behçet’s disease presenting with unilateral ptosis and facial paresis due to an intracranial mass lesion. A 25-year-old male patient with a history of Behçet’s disease presented with headache, vertigo, double vision, ptosis in his right eyelid and slurred speech. Cranial magnetic resonance imaging scan revealed a right-sided capsulothalamic lesion, which was extending to the right cerebral pedicle, pons and superior cerebellar pedicle. This lesion was interpreted as neuro-Behçet’s disease involvement of central nervous system. Cerebral mass- like lesion is a rare form of neuro-Behçet’s disease. Review of the literature revealed a limited number of cases. Ptosis related with Behçet’s disease is also a very rare presentation. This case shows that this symptom might be a part of the clinical presentation of neuro-Behçet’s disease.